Benchmarking jako instrument poprawy konkurencyjności przedsiębiorstw - Kuczewska, Joanna (Benchmarking - the Instrument of Enterprises' Competitiveness Improvement, 2006)
Benchmarking has been defined as a continuous, systematic process for comparing performances of organizations, functions or processes against the best in world, aiming not only match those performance levels, but to exceed them. Benchmarking allows to analyse and improve key business processes, performance, profitability and market shares. It allows improving competitiveness. The benchmarking process is of significant potential benefit to industry when used as a continuous, dynamic process where areas for potential changes are identified and improvements are monitored.Benchmarking is often identified with the competitive position analysis. The competitive position analysis assesses the final company's competitive conditions and it is classified as a static method. Benchmarking is a continuous, systematic process for changes introducing. It improves management processes and is classified as a dynamic method.The benchmarking process generally consists of four stages: planning, information/data collecting, analyzing and adapting which are combined with different benchmarking models e.g. Camp R.C. Model, Watson G.H. Model, IBC Model and The Benchmarking Wheel Model.Summing up, benchmarking is a dynamic method of company's management processes improvement. It assesses the crucial management areas, ensures the permanent effectiveness improvement and applies the "best in class" solutions. The benchmarking process and other methods of competitiveness improving are complementary.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 480-491